Validation and Psychometric Properties of One School, Many Differences. (3rd July 2019) - Tadlock-Marlo, Rebecca L.; Hill, Nicole R.
Abstract: Counselor educators must prepare school counselor trainees to celebrate diversity. Via confirmatory factor analysis and item response theory, this research indicates school counselor multicultural competence is a stable 4-domain model consisting of assessment of school environment, reflection of personal culture, development of interpersonal relationships, and collaboration. Implications for educators and practitioners are described.